Samarium (II) iodide cyclizations of halo- and carbonylhydrazones. - Sturino, Claudio F. (University of Ottawa (Canada), 1995)
The preparation of a variety of halo and keto C=N containing systems for use in free radical cyclization is described. The 6-exo radical cyclization of bromo oxazolines (A) was first examined under standard tin hydride conditions, but only reduction products were isolated. The use of syringe pump techniques also gave only the reduced product. The use of Bu$\sb3$SnD demonstrated that a 1,5-hydrogen shift was responsible for the premature quenching of the alkyl radical. A related bromo-oxazoline was prepared which was not capable of undergoing a 1,5-hydrogen shift after generation of the radical was prepared, but it did not cyclize under any conditions employed. Thus attention was directed towards hydrazones (B), whose reactivity in radical cyclizations has received little attention. This study has shown that simple bromo-hydrazones underwent an extremely efficient radical cyclization to give high yields of the cyclopentyl and cyclohexyl hydrazines (C). Ketyl radicals were generated from the corresponding aldehydes and ketones (D) using SmI$\sb2$/HMPA and their intramolecular cyclizations onto hydrazones was shown to be a facile and high yielding process. Unlike the alkyl radical cyclizations, the ketyl radical reactions were more selective at higher temperatures. Thus at room temperature, the 5-exo ketyl radical cyclization gave $>$15:1 selectivity in favour of the isomer with the hydroxy and hydrazino groups trans (E). The difference between the ketyl and alkyl cyclizations is even more notable in the 6-exo cyclizations. These reactions gave generally modest selectivities in the alkyl series but the 6-exo ketyl radical cyclizations were highly selective at all temperatures examined. The products of these reactions, cyclic $\beta$-hydroxy hydrazines, are closely related to an important class of natural products, $\beta$-hydroxy amines. Thus methods for cleaving the N-N bond to yield the corresponding amines were examined. Having developed conditions for cleavage of the N-N bond, the utility of the method was demonstrated in a brief synthesis of a penta-substituted $\beta$-hydrazino alcohol which is related to the allosimizoline class of antifungal and insecticidal agents. L-Xylose was used as the starting material for the preparation of the chiral hydrazone-aldehyde. In the second portion of this thesis, we describe the determination of the rate constant for the 5 and 6 exo cyclizations of alkyl radicals using radical clock techniques. Thus a halo-hydrazone (F) was prepared that contained an alkene suitably positioned for a 5-exo hexenyl-type cyclization. The corresponding 5-exo hydrazone cyclization was surprisingly too fast to be measured with the 5-hexenyl clock. The rate constant for this fast reaction could be determined by running the cyclization in concentrated Bu$\sb3$SnH and measuring the amounts of cyclized vs. reduced products. This intermolecular clock gave a rate constant for the 5-exo cyclization of k$\sb{\rm cis}$ = 1.1 $\times$ 10$\sp8$s$\sp{-1}$ and k$\sb{\rm trans}$ = 4.6 $\times$ 10$\sp7$s$\sp{-1}$ at 80$\sp\circ$C, which is approximately 200 times faster than the corresponding alkene cyclization. From this data we calculated that a cyclization run in neat Bu$\sb3$SnH at 80$\sp\circ$C would give a 12:1 ratio of products in favour of the cyclized product. A related system (G) was prepared to test the 5 and 6 exo ketyl radical cyclizations. As in the simple alkyl radical systems, the hydrazone proved to be a more efficient radical acceptor than the corresponding alkene. (Abstract shortened by UMI.)(DIAGRAM, TABLE OR GRAPHIC OMITTED...PLEASE SEE DAI)
Keywords: Chemistry, Organic.